2017
DOI: 10.1074/jbc.c117.794982
|View full text |Cite
|
Sign up to set email alerts
|

A dual agonist of farnesoid X receptor (FXR) and the G protein–coupled receptor TGR5, INT-767, reverses age-related kidney disease in mice

Abstract: Even in healthy individuals, renal function gradually declines during aging. However, an observed variation in the rate of this decline has raised the possibility of slowing or delaying age-related kidney disease. One of the most successful interventional measures that slows down and delays age-related kidney disease is caloric restriction. We undertook the present studies to search for potential factors that are regulated by caloric restriction and act as caloric restriction mimetics. Based on our prior studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 38 publications
1
43
1
Order By: Relevance
“…In the early stages of disease, tubular growth can result in an increase in kidney weight (especially the proximal tubule which comprises ∼90% of the renal cortex) and may be associated with poor renal outcome . In addition, primary increases in renal expression of SGLT2 and/or SGLT1 have been observed in diabetic mice . Studies in T2DM patients identified that renal SGLT1 mRNA expression was markedly increased and SGLT2 mRNA levels (not significantly) down‐regulated .…”
Section: Targeting Sglts For Glycaemic Controlmentioning
confidence: 99%
“…In the early stages of disease, tubular growth can result in an increase in kidney weight (especially the proximal tubule which comprises ∼90% of the renal cortex) and may be associated with poor renal outcome . In addition, primary increases in renal expression of SGLT2 and/or SGLT1 have been observed in diabetic mice . Studies in T2DM patients identified that renal SGLT1 mRNA expression was markedly increased and SGLT2 mRNA levels (not significantly) down‐regulated .…”
Section: Targeting Sglts For Glycaemic Controlmentioning
confidence: 99%
“…Activating the bile acid‐activated nuclear hormone receptor FXR, and the G protein coupled receptor TGR5, reduces several diseases of aging, including chronic liver and kidney disease as well as diabetes (Rizzo et al, ). Chronic treatment of aging mice with INT‐767d could, in principle, retard these diseases as well as other deleterious aspects of aging (Fiorucci, Mencarelli, Palladino, & Cipriani, ; Hylemon et al, ; Wang et al, ). Dwarf mouse models with increased lifespan also have increased serum and liver bile acid levels and FXR activation, which supports this idea (Gems, ).…”
Section: Introductionmentioning
confidence: 99%
“…The rationale is that activation will improve hepatic recirculation of bile acids, reduce gut permeability, and also exert anti-inflammatory effects. [42][43][44][45] Chronic alcohol use changes the composition of the gut microbiome and restoration of the microbial dysbalance is an attractive therapeutic approach. 46,47 An early reduction in Akkermansia has been identified after short-term alcohol feeding in mice and the same defect was seen after chronic alcohol use in mice and humans.…”
Section: Understanding Disease Pathology Informs Strategies For Drug mentioning
confidence: 99%